Effect of Internal Heat Generation on Heat Transfer of Trihybrid Nanofluid in an Open Enclosure with a Hot Baffle - Rajab Alsayegh (Results in Engineering)
This study investigates natural convection (NC) heat transfer (HT) in a two-dimensional square cavity filled with a triphasic hybrid nanofluid (HNF) mixture (Al₂O₃, Cu, and MWCNT dispersed in thermal oil). The analysis examines the combined effects of thermocapillary forces (Marangoni number, Ma), buoyancy forces (internal and external Rayleigh numbers, RaI and RaE), and internal heat generation. Numerical simulations are conducted to explore how these parameters influence fluid flow and thermal behaviour. The results indicate that negative Ma values enhance the HT due to the cooperative effect of thermocapillary and buoyancy forces, while positive Ma values tend to hinder convective motion, leading to either reduced or stabilized heat transfer. Increasing RaE from 5,000 to 50,000 improves heat transfer by up to 58%, whereas varying Ma from -10,000 to 10,000 results in a more moderate 20% enhancement. Additionally, at high RaI values, thermal forces dominate over viscous and thermocapillary effects, further intensifying convection. The presence of hybrid nanoparticles significantly improves heat transfer efficiency, with a 6% volumetric concentration increasing the average Nusselt number by 23.3%. A V-shaped trend in Nu as a function of Ma is observed, highlighting the complex interplay between thermocapillary and buoyancy forces.